Implementasi Metode Propotional, Integral, Derifative (PID) Sebagai Kontrol Kapal Autonomous Dengan Sistem Waypoint Untuk Wahana Batimetri - Amsyafi Putra, Dedy Prayogy; Suryadhi, Suryadhi; Bintoro, Rudi Siap (Universitas Pendidikan Nasional, 2021)
Indonesia is the world's largest island nation with many islands and more seas than land. Because of the size of the Indonesian sea, oceanographic science is needed. Oceanographic learning involves the study of the underwater depths of the batimetric sciences. Batimetric science is crucial because it studies underwater depth. Batimetric processes in Indonesia today generally employ large vessels with manual control, resulting in the skill required of drivers at risk for obtained track data. With the problem, it has been designed to disrupt the autonomous control system with a pid waypoint system that would provide stable direction for the ship. The control system USES the arduino microcontroller which is used for processing data. The data obtained are data coordinates obtained from the GPS and the ship's navigation data obtained from the compass sensors. The data obtained will be processed and applied to pid methods. Of the pid process can be generated the degree degree required to power the servo motor connected to the ship's rudder. In this research USES four coordinate points of starting point, first goal point, second point of destination, and third point of goal. Once it reaches the third point of destination, the ship will return to its starting point. From the results of the testing done, the result is a kostanta pid score of KP =8, ki =5, kd = 3.5. Tests enabled the system that kept the ship's course steady as it should. So the ship goes on track.